Integrative Approach in Teaching English for Professional Purposes - V. A. Sokolova; I. V. Titova (Высшее образование в России)
The article discusses the need for an integrative approach in teaching Business English, aimed at forming and developing professional competencies of a future graduate in the field of management. The applied aspect of the integrative approach means implementing the principle of integration in all parts of the educational process. In this study, it concerns the formation of professional competencies during the process of learning a foreign language. The basis of the successful implementation of an integrative approach at all levels is adding a reflective component, forming of reflective position of a student. It helps analyze and order all the elements and stages of the studying activity from goal setting to result achieving; it also helps students realize themselves as active participants of the studying process. Today, due to various factors and reasons, the potential of the discipline “Business Foreign Language” in forming professional competencies often remains unrealized. The course developed allows to fully reveal its opportunities of forming professional competencies for a future manager. The course is focused on developing skills in a foreign language and professional training of students in such field of study as “Management”. This contributes to the students’ personal and professional growth. This is achieved due to the course’s content and structure, when the general concept of management and its functions being considered sequentially and logically. Including the reflective component into the studying process allows not only the teacher but also the students themselves follow the level of progress and the degree of achieving the goals set by them.